Analysis of students' level of understanding about lgbt by gender - Nurfarida Deliani; Silfia Hanani; Kunalan Kuriaya; Khairunnas Rajab; Abdurrahman Abdurrahman; Syawaluddin Syawaluddin; Febri Wandha Putra; Khadijah Lubis (Konselor, 2021)
The phenomenon of the number of LGBT cases that appear among teenagers motivates this research. Therefore, the purpose of this research is to find out how students understand about LGBT. This research is a quantitative research using a quantitative approach. Students from class X Madrasah Aliyah in the city of Padang were the subject of this study. The sampling technique used was purposive sampling with criteria 1) students who did not live with their parents, and 2) students who had more friends of the same sex than those of different genders. The instrument used is a questionnaire on students’ understanding of LGBT and the Likert model scale. The data processing of this research used statistical fit analysis through the Rasch Model application and the t-test using the SPSS application. The results of the study show 1) The instruments used to measure students’ understanding of LGBT have good quality to be used in revealing students’ understanding of LGBT; 2) overall, students’ understanding of LGBT is in the pretty good category and a few students understand LGBT, which is in the low and good categories; and 3) There are differences in understanding of LGBT between male students and female students.